Frontispiece: Added‐Value Surfactants. Issue 71 (18th December 2018) - Polarz, Sebastian; Kunkel, Marius; Donner, Adrian; Schlötter, Moritz
Abstract : Surfactants are functional molecules, which are used to stabilize interfaces of all kind, for example, in foams. They are produced in large amounts by the chemical industry and represent an inherent part of everyone′s daily routine. Next‐generation surfactants contain at least one additional feature, for example catalytic activity or special redox properties. Another class offers smart properties like thermoresponsivity. Ultimately, the surfactant′s head could reach a high degree of multifunctionality, "comparable" to a swiss army knife. For a comprehensive discussion see the Minireview by S. Polarz et al. on page 18842 ff.